The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/pai.12321
|View full text |Cite
|
Sign up to set email alerts
|

Childhood body mass index and wheezing disorders: a systematic review and meta‐analysis

Abstract: Abstract:BACKGROUND: )t has been claimed that overweight obesity and childhood asthma and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 78 publications
0
45
1
1
Order By: Relevance
“…Several previous studies reported effects of rapid weight gain and larger weight on the development of wheezing in children,3–11 27 28 but other studies have failed to replicate these findings 12–14. Discrepancies between studies could be partially due to methodological issues, such as different outcome definitions, growth modelling methods and periods of exposure and outcome assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies reported effects of rapid weight gain and larger weight on the development of wheezing in children,3–11 27 28 but other studies have failed to replicate these findings 12–14. Discrepancies between studies could be partially due to methodological issues, such as different outcome definitions, growth modelling methods and periods of exposure and outcome assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Potential predictors of asthma diagnosis were identified a priori through a literature review and were included as covariates in the analysis. Child factors included age, sex, and body mass index (zBMI) . A parent completed questionnaire, adapted from the Canadian Community Health Survey, was used to define parental and household factors which included median household income, parental smoking, child's history of atopy (eczema or atopic dermatitis), child's history of allergies, daycare attendance, and family history of asthma .…”
Section: Methodsmentioning
confidence: 99%
“…), многие из которых синтезируются и секретиру-ются клетками жировой (адипозной) ткани [4,5] и поэтому названы адипокинами, включая IL-6, IL-10, эотаксин, фактор некроза опухоли α, трансфор-мируемый фактор роста β1, C-реактивный протеин, лептин и адипонектин. Наконец, было идентифи-цировано, что идентичные локусы генома человека отвечают как за БА, так и за ожирение [6][7][8][9][10][11].…”
Section: ключевые слова: бронхиальная астма избыточная масса тела сunclassified